2012
DOI: 10.1016/j.gie.2011.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Polysomy and p16 deletion by fluorescence in situ hybridization in the diagnosis of indeterminate biliary strictures

Abstract: FISH significantly improves the diagnostic accuracy of brush cytology in indeterminate biliary strictures. In our series, the addition of 9p21 deletion to FISH polysomy and cytology further improved sensitivity. This suggests that 9p21 deletion may be added to the diagnostic criteria in indeterminate strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 20 publications
5
84
0
1
Order By: Relevance
“…Applying fluorescence in situ hybridisation (FISH), which uses fluorescently-labelled DNA probes to detect aneuploidy in cells, reportedly confirmed cancer in 60% of patients in whom standard brush cytology was negative 50. A subsequent study confirmed the ability of FISH to improve the diagnostic accuracy in indeterminate biliary strictures, increasing the sensitivity of brush cytology from 21% to 58% 56. Including the presence of 9p21 deletion increased the sensitivity to 89%.…”
Section: Diagnosismentioning
confidence: 98%
“…Applying fluorescence in situ hybridisation (FISH), which uses fluorescently-labelled DNA probes to detect aneuploidy in cells, reportedly confirmed cancer in 60% of patients in whom standard brush cytology was negative 50. A subsequent study confirmed the ability of FISH to improve the diagnostic accuracy in indeterminate biliary strictures, increasing the sensitivity of brush cytology from 21% to 58% 56. Including the presence of 9p21 deletion increased the sensitivity to 89%.…”
Section: Diagnosismentioning
confidence: 98%
“…A recent report studied the additional value of including deletion of 9p21 (p16) in the diagnostic criteria of FISH for malignant biliary strictures. 40 This addition significantly improved the sensitivity of FISH from 47% to 84%.…”
Section: Ancillary Cytology Techniquesmentioning
confidence: 99%
“…DNA FISH applied on cytology specimen can facilitate the diagnosis of indeterminate biliary strictures, associated with CCA. 13,33,34 Several studies have shown that chromosomespecific probes (chromosome 3, 7, and 17) to detect polysomy, serve as an indicator of chromosomal instability. The sensitivity of conventional cytology varied from 4% to 21% and increased to 35% to 60% when combined with assessment for polysomy with FISH while preserving the specificity of conventional cytology.…”
Section: Polysomymentioning
confidence: 99%
“…The diagnosis of adenocarcinoma in indeterminate biliary strictures can improve from 58% to 89% with the detection of p16 deletion by FISH in addition to polysomy, as compared with 21% with conventional cytology. 33 Both promoter hypermethylation (76%-83%) and genetic mutation or deletion have been described (20%-80%) in biliary cancers. [56][57][58][59] Using methylation-specific polymerase chain reaction, bile specimen of 71 patients with biliary disease were evaluated (including 11 patients with PSC).…”
Section: P53 In Psc-associated Ccamentioning
confidence: 99%